2021
DOI: 10.2147/cia.s320900
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Health Literacy, Self-Efficacy, Social Support, and Oral Health Care Behaviors Among Elderly in Northern Border Community Thailand

Abstract: Background: Oral health problems among elderly people are an important public health issues worldwide. Oral healthcare is essential to the health and well-being of elders and is one of the key indicators determining their quality of life. This research aimed to study oral health literacy, selfefficacy, social support, and demographic characteristic factors associated with the oral health care behaviors of elderly people living in the rural areas of northern Thailand. Methods: This research was a cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Moreover, there is a great imbalance in the distribution of dental practitioners among the provinces in China, neither the number of dental practitioners nor the number of dental visits is enough to meet the dental care demand in China as compared to developed countries [23]. There are also some personal factors, such as personal characteristics, health needs, and health behaviors [9,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there is a great imbalance in the distribution of dental practitioners among the provinces in China, neither the number of dental practitioners nor the number of dental visits is enough to meet the dental care demand in China as compared to developed countries [23]. There are also some personal factors, such as personal characteristics, health needs, and health behaviors [9,11].…”
Section: Discussionmentioning
confidence: 99%
“…A study in Iran showed that 62.5% of adult patients had an adequate oral health literacy level [9]. However, a survey of older adults in Thailand showed the majority of participants (85%) had inadequate functional health literacy, [11]. Previous studies show that people with limited OHL levels had poor periodontal health [12].…”
Section: Introductionmentioning
confidence: 99%
“…Oral healthcare behavior includes personal oral behavior, food consumption behavior, and medical care behavior [ 10 ]. Sociodemographic factors associated with oral healthcare behavior are age, sex, and educational level [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas policy strategies to promote OHB in the adult population have traditionally been through encouraging brushing and flossing practices at the individual level, a growing number of studies begin to explore the more distal and structural determinants of OHB (Vasiliou et al, 2016). The role of psychosocial factors in promoting OHB draws more interest from researchers, such as oral health beliefs (Im et al, 2015), job stress (Ghulam et al, 2018), social support (Khamrin et al, 2021) and perceived behavioral control (PBC) (Brein et al, 2016). Social support as a way to promote OHB received a lot of attention as it is easy to provide.…”
Section: Introductionmentioning
confidence: 99%